Faktor-Faktor Yang Berhubungan Dengan Perilaku Hidup Bersih Dan Sehat (PHBS) Dimasa Pandemi Covid-19 Pada Warga Cilodong Depok - Anisa Derilliani; Milla Evelianti Saputri; Rosmawaty Lubis (Malahayati Nursing Journal, 2022)
ABSTRACT Coronavirus Disease 2019is a contagious disease. This virus is a new type of coronavirus and has never been identified in humans before. Symptoms of Covid-19 are fever, cough and shortness of breath. One way that can be done in preventing the transmission of Covid-19 is the Clean and Healthy Lifestyle (PHBS). Several factors that can affect PHBS are knowledge, the role of health workers and infrastructure. Purpose to identifying factors related to clean and healthy living behavior (PHBS) during the COVID-19 pandemic for residents of the Cilodong Depok area in 2022. The design of this research is descriptive with a cross sectional approach. The sampling technique used was total sampling. The sample in this study amounted to 50 people, the knowledge questionnaire has been tested for validity and reliability with a cronbach's alpha value of 0.946, the role of health workers with a cronbach's alpha value of 0.838, infrastructure facilities with a cronbach's alpha value of 0.845 and a Clean and Healthy Life Behavior (PHBS) questionnaire during the Covid Pandemic. -19 with Cronbach's alpha value of 0.903. PHBS behavior of the majority of respondents (78%) is good.The results of chi square (p 0.05) obtained a knowledge questionnaire p = 0.009, the role of health workers p = 0.008, and infrastructure p = 0.021 so that H0 is rejected meaning that there is a relationship between knowledge, the role of health workers and infrastructure with Clean Living Behavior and Healthy (PHBS) during the Covid-19 Pandemic. There is a relationship between knowledge, the role of health workers and infrastructure with Clean and Healthy Life Behavior (PHBS) during the Covid-19 Pandemic. For the community, it is expected to further improve PHBS during the covid-19 pandemic in order to prevent the transmission of covid-19. Keywords: PHBS, Covid-19, knowledge, role of health workers, infrastructure ABSTRAK Coronavirus Disease 2019 merupakan penyakit yang menular. Virus ini adalah coronavirus jenis baru dan belum pernah diidentifikasi pada manusia sebelumnya. Tanda gejala Covid-19 adalah demam, batuk dan sesak napas. Salah satu cara yang dapat dilakukan dalam pencegahan penularan Covid-19 ini yaitu Perilaku Hidup Bersih dan Sehat (PHBS). Beberapa faktor yang dapat mempengaruhi PHBS adalah pengetahuan, peran petugas kesehatan dan sarana prasarana. Tujuan untuk mengidentifikasi Faktor-faktor yang berhubungan dengan perilaku hidup bersih dan sehat (PHBS) di masa pandemi covid-19 pada warga wilayah Cilodong Depok 2022. Desain penelitian ini adalah deskriptif dengan pendekatan cross sectional. Teknik pengambilan sampel menggunakan total sampling. Sampel pada penelitian ini berjumlah 50 orang, kuesioner pengetahuan telah diuji validitas dan reabilitas dengan nilai cronbach’s alpha 0,946, peran petugas kesehatan dengan nilai cronbach’s alpha 0,838, sarana prasarana dengan nilai cronbach’s alpha 0,845 dan kuesioner Perilaku Hidup Bersih dan Sehat (PHBS) dimasa Pandemi Covid-19 dengan nilai cronbach’s alpha 0,903. Perilaku PHBS sebagian besar responden (78%) baik. Hasil chi square (p0,05) didapatkan kuesioner pengetahuan p=0,009, peran petugas kesehatan p=0,008, dan sarana prasarana p=0,021 sehingga H0 ditolak artinya ada hubungan antara pengetahuan, peran petugas kesehatan dan sarana prasarana dengan Perilaku Hidup Bersih dan Sehat (PHBS) dimasa Pandemi Covid-19. Ada hubungan antara pengetahuan, peran petugas kesehatan dan sarana prasarana dengan Perilaku Hidup Bersih dan Sehat (PHBS) dimasa Pandemi Covid-19. Bagi masyarakat diharapkan lebih meningkatkan PHBS dimasa pandemi covid-19 guna mencegah penularan covid-19. Kata Kunci: PHBS, Covid-19, pengetahuan, peran petugas kesehatan, sarana prasarana